Characterization and Utilization of Organo-Refined Extract in Metallurgical Coke Making. Issue 2 (17th February 2018) - Nag, Debjani; Biswas, Pinakpani; Dash, Pratik Swarup; Chandaliya, Vimal Kumar; Sahoo, P. P.; Saxena, V. K.; Chandra, S.
ABSTRACT: High-ash Indian coals and washery discards were extracted using an organic solvent. Complete characterization study was carried out in order to measure its coking potential. The study revealed that swelling and thermoplastic properties of the extracts are better as compared to the parent coals. A new concept for studying the thermoplastic behavior of coal is introduced to access the coking potential of parent and extracted coal. A series of carbonization tests was performed considering organic extracts as one of the blend components. The carbonization study reflects that the addition of an optimum amount of extracts in the base-coal blends helped in improving the properties of metallurgical coke.